Antifungal property of acrylic denture soft liner containing silver nanoparticles synthesized in situ. (March 2021) - Deng, Jie; Ren, Lingyan; Pan, Yahui; Gao, Hai; Meng, Xiangfeng
Abstract: Objectives: Denture soft liner is applied to relieve pain from candida-induced denture stomatitis and promote healing, but with shortage of antifungal activity and easily harbors fungi. To overcome this problem, the in-situ method was used to synthesize silver nanoparticles (AgNPs) in acrylic soft liner to obtain antifungal effects. Methods: Acrylic soft-liner with various weight percentage of silver 2-ethylhexanoate (0%, 0.1 %, 0.2 %, 0.3 %) were prepared in 10 mm × 10 mm × 3 mm. After chemical polymerization, the diameter of AgNPs synthesized in situ and the degree of conversion of each group were measured. After 3, 7, and 14 days of storage in water, the antifungal rate (AFR) of in vitro direct contact antifungal assays and the antifungal test of non-cumulative extract solution were measured respectively. The release profiles of silver ions from the specimen within 14 days were also evaluated. Results: Evenly distributed AgNPs (4.7 nm–5.3 nm) were observed, and the degree of conversion had no significant difference among these groups. The AFR increased as the silver concentration rose, while decreasing with the storage time. After 14 days of water storage, the AFR of 0.2 % and 0.3 % groups still reached 63.38 % and 75.51 %, respectively. The non-cumulative extract solution had no antifungal effect. Conclusions: Within the service life, the acrylic soft liner containing AgNPs synthesized in situ had effective control of Candida albicans through direct contact. Clinical Significance: This study suggests that AgNPs synthesized in situ may be an effective strategy in modifying acrylic denture soft liner to treat and prevent denture stomatitis.